Development of non-ICT company procurement and shipment portal using referenced mobile application - Chin, Pey Mian (2023)

(untitled)
Many organisations have adapted the current digital technology to transform their business models to gain competitive advantage in the marketplace. Euro Potential Sdn Bhd is a non-IT company trying to digitalise its business operations. Currently, the company operates a traditional business model which the salesperson communicating with customer through phone calls, physical meetings, or messengers. In this project, the web portal is developed to solve the problems faced by the company. The Agile methodology was implemented to match the project objectives. Agile methodology with multiple iterations planned for the project development. Each iteration will focus on the development of the module. This project has divided into several modules which are Procurement and Shipment module, Quote module, Consumption module, Project Development module and Product module. The Kanban methodology was utilised as the Agile framework to manage the development progress. The technology used to develop the system is the MERN stack. MERN stands for MongoDB, Express, React.js, Node, which are the four key technologies built as a three-tier architecture. In conclusion, the primary module of the project that will be established for management and salesperson to manage order progress. The module used to solve the company's difficulties and achieve the transformation of business operations.